On non-densely defined invariant Hermitian contractions - Bekker, M. B. (Methods of Functional Analysis and Topology, 2007)
We consider a non-densely defined Hermitian contractive operator which is unitarily equivalent to its linear-fractional transformation. We show that such an operator always admits self-adjoint extensions which are also unitarily equivalent to their linear-fractional transformation.